A piezoelectric energy harvester for collecting environment vibration excitation. (November 2022) - He, Lipeng; Gu, Xiangfeng; Hou, Yi; Hu, Renhui; Zhou, Jianwen; Cheng, Guangming
Abstract: This paper presents a harvester that collects vibrational energy. The piezoelectric sheet deforms under mass inertia and then generates electricity according to the piezoelectric effect. At the same time, when designing the equipment, the incentive model is selected as the non-contact type to avoid mechanical collision and wear inside the structure and improve the service life of the device. An equivalent damping analysis is performed for the cantilever and combined with the control equations of the Lagrangian. The simulation analysis obtains the native frequency of the rectangular and circular piezoelectric sheets under the mode analysis. Through experimental proof that the device reaches the maximum output voltage 67.19 V when magnet 1 in the mass mutually repels magnet 1 in the housing and magnet 2 in the mass and magnet 2 in the housing. For an external resistance of 10 KΩ, the maximum power output of the device is 165 mW. The device can convert the vibrational energy in the environment into electricity and supply power to other devices through circuit storage.